Critical Factors for Account Representative Success in Reaching Tax Revenue Targets - Muhammad Afdhal Usman; Haliah Haliah; Andi Kusumawati (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Account Representatives are the foundation for each Tax Office, Regional Office, and even the Directorate General of Taxes in achieving tax revenue because it functions as a supervisor for taxpayers in performing their tax compliance. Against the background of the importance of achieving tax revenue and the important role of Account Representatives in achieving the tax revenue target, it is deemed necessary to know what factors determine the success of the Account Representative in achieving the tax revenue target in Indonesia. To find out these factors, qualitative research was carried out using a case study approach through in-depth interviews with 24 informants from internal and 5 informants from external of the Directorate General of Taxes, by previously conducting a preliminary questionnaire. Based on this, it was found that several factors influence or become determining factors for the Account Representative's success in achieving the tax revenue target for which they are responsible, including motivation at work, understanding of regulations, ability to communicate, availability, and accuracy of data, superior and organizational support, IT facilities and applications, profiling capabilities, mapping and business processes of taxpayers, completeness and clarity of tax regulations, placement and mutation, and awareness of taxpayers.